Something deep - Othman, Laylah Ali (Abuja, Nigeria Kurdan Publishing House, 2017)
A fictitious story on how six year old Amina lived with her family in Sokoto. The only thing that worried her was going to school and finding ways to be mischievous until their gateman began summoning her to his room and isolated corners. The book chronicles the account of Amina's molestation and the hell that broke loose in her mind after that .
oif 10/07/2018
Loans
Keywords: Fiction